Sporotrichosis in a 9-month-old baby boy: a rare presentation - Vivian M. S. C. Silva; Hugo M. Faver; Violeta N. Gushiken-Duarte; Camila A. Alves; Angela C. Nascimento; Andressa B. Simões; Sara M. G. F. Murta; Igor B. Cursi (Sociedade Portuguesa de Dermatologia e Venereologia, 2024)
Sporotrichosis is a subacute to chronic mycosis caused by species of the genus Sporothrix. While the lymphocutaneous form predominates in most cases, immunocompromised individuals may present with disseminated variants. It is more prevalent in adults and rare in infants, with poorly studied risk factors and epidemiological aspects in this age group. We describe a case of sporotrichosis infection in a 9-month-old child, presenting with two progressively growing nodules, soft in consistency, located in the right cervical and pre-auricular regions, associated with a decline in general condition and fever over a month's duration. Despite multiple oral antibiotics, there was no lesional improvement. Aspiration of one of the nodules, and culture of the secretion revealed Sporothrix. The patient was then treated with oral itraconazole, leading to regression of the lesions within 2 months. The identification of the transmission agent in this case was not possible. This report aims to broaden the understanding of sporotrichosis manifestation in infants and to provide valuable insights for the enhancement of specific preventive, diagnostic, and therapeutic strategies for this age group of dermatological patients.